L’influence d’innovations pédagogiques sur le profil motivationnel et le choix de stratégies d’apprentissage d’étudiantes et d’étudiants d’une faculté d’ingénierie - Anastassis Kozanitis (Revue Internationale de Pédagogie de l’Enseignement Supérieur, 2010)
The study’s aim is to establish a classification of motivational characteristics and learning strategies used by students within three different instructional approaches : lectures, project based-instruction, and web-based instruction. A self-report questionnaire was administered to 494 undergraduates. Results of the cluster analyses reveal that students attending project-based instruction and lecture method show higher levels of motivation than those attending web-based instruction. Students in lecture method and web-based instruction turn more often to memorisation, revision and organisation strategies, while project-based learning promotes the use of effort and time regulation strategies. A discussion seeks to explain the observed differences.